Інструкція з нормування витрат теплової енергії на продукцію підприємств молочної промисловості - Баранов, Володимир Іванович (My University, 1998)
Інструкція укладена у відповідності до постанови Кабінету Міністрів України від 15.07.97 № 786 "Про порядок нормування питомих витрат паливно-енергетичних ресурсів у суспільному виробництві" та "Основних методичних положень з нормування питомих витрат паливно-енергетичних ресурсів у суспільному виробництві" (Затверджено наказом Держкоменергозбереження від 14 жовтня 1997 року № 93). В інструкції подані склад і методика визначення технічно і економічно обґрунтованих норм витрат теплової енергії на продукцію, що виробляється підприємствами молочної промисловості, а також наведені приклади розрахунків норм та довідкові дані. Інструкція призначена для практичного використання підприємствами молочної промисловості та плануючими організаціями при нормуванні і впровадженні режимів економії теплової енергії. The instruction has been prepared in accordance with a decree of Cabinet of Ministers of Ukraine №786 dated 15.07.97 “Regarding to the order for rationing of specific consumption of fuel and energy resources in public production” and according to “The main methodological approaches for rationing of specific consumption of fuel and energy resources in public production” (approved by the order of State agency on energy efficiency and energy saving of Ukraine №93 dated 14.10.1997). The instruction provides the structure and the methodology to determine expenditure rates of thermal energy for the product in dairy industry based on economic and financial grounds. The instruction also contains respective examples of calculations of expenditure rates and the reference information. The instruction is dedicated for practical use on enterprises of dairy industry and by planning organizations or divisions in the process of rationing and implementation of energy saving modes.
Keywords: нормування питомих витрат паливно-енергетичних ресурсів; теплова енергія; питомі витрати енергії; молочна промисловість; rationing of specific consumption of fuel and energy resources; thermal energy; specific energy consumption; dairy industry